Nano cellulose / aluminum foil composite non-woven fabric heat preservation bag and preparation method thereof

By introducing the synergistic effect of metal organic frame compounds (MOFs) and cerium humate into nanocellulose/aluminum foil composite nonwoven fabrics, a multiple coordination network is constructed, which solves the problem of insufficient interface bonding strength, and achieves the efficient insulation performance and long life of the material, and maintains environmental protection and economicality.

CN120396472AInactive Publication Date: 2025-08-01WENZHOU WANJING NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510594203.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-08-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Among the existing nanocellulose/aluminum foil composite nonwoven materials, the interface bonding strength between the nanocellulose and the aluminum foil is insufficient, resulting in layering and peeling, affecting the insulation performance and service life. The traditional modification method has problems such as poor environmental protection and high cost.

Method used

Metal organic frame compounds (MOFs) are used to form a synergistic interface structure with cerium humate. By building a multiple coordination network between nanocellulose and aluminum foil, the interface bonding strength is enhanced, and the material composite is achieved through polyvinyl alcohol (PVA) adhesive and hot pressing process.

Benefits of technology

The interface bonding strength between nanocellulose and aluminum foil is significantly improved, the service life of the material is extended, the insulation performance is optimized, and the environmental protection and economicality of the material is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120396472A_ABST
    Figure CN120396472A_ABST
Patent Text Reader

Abstract

The invention discloses a nanocellulose / aluminum foil composite non-woven fabric thermal insulation bag and a preparation method thereof. The invention relates to a nano cellulose / aluminum foil composite non-woven fabric thermal insulation bag, which comprises the following components: a polypropylene non-woven fabric base material; the composite interface layer is formed by nanocellulose, a metal organic framework compound (MOFs) and cerium humate; an aluminum foil reflecting layer; the metal organic framework compound (MOFs) and the cerium humate form an interface structure, so that the interface bonding strength between the nanocellulose and the aluminum foil is improved. The preparation method of the non-woven fabric thermal insulation bag is used for preparing the non-woven fabric thermal insulation bag. The heat preservation bag and the preparation method thereof have the following beneficial effects that the technical problem that the interface bonding strength between existing nano cellulose and aluminum foil is insufficient is effectively solved, the heat preservation performance of a product is improved, and the service life of the product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal insulation material preparation, and particularly relates to a nano-cellulose / aluminum foil composite non-woven thermal insulation bag and a preparation method thereof. This thermal insulation bag is mainly applied to the thermal insulation transportation of food, medicine and daily necessities. Background Art

[0002] The field of thermal insulation materials has always been an important research direction in the field of materials science and engineering. In particular, lightweight and efficient thermal insulation bag materials have a wide range of application requirements in the transportation of food, medicine and daily necessities. Traditional thermal insulation bags mainly use materials such as expanded polystyrene and polyurethane foam. Although they have certain thermal insulation properties, they have problems such as poor environmental friendliness and difficulty in recycling. In recent years, thermal insulation bags based on non-woven fabrics have gradually become a research hotspot due to their advantages such as light weight, good flexibility and low cost.

[0003] The development of non-woven thermal insulation materials has gone through multiple stages. The initial non-woven thermal insulation bags mainly adopted a composite structure of single-layer non-woven fabric and aluminum foil, relying on the reflection of aluminum foil to block heat radiation. Subsequently, the technological development introduced a multi-layer structure design, and multiple thermal insulation layers were formed by adding materials such as bubble film and cotton wool between the non-woven fabric layers to further improve the thermal insulation effect. However, such materials still face problems such as low thermal insulation efficiency and short service life.

[0004] In recent years, with the development of nanotechnology, nano-cellulose, as a renewable material derived from natural cellulose, has the characteristics of low density, large specific surface area and excellent mechanical properties, and is widely used in the preparation of composite materials. Aluminum foil, due to its excellent heat reflection performance, is often used as a heat insulation material. The composite application of nano-cellulose and aluminum foil in non-woven thermal insulation materials can combine the advantages of both and achieve excellent thermal insulation performance.

[0005] However, the current research on nano-cellulose / aluminum foil composite non-woven thermal insulation materials still faces multiple technical challenges. The primary problem is the insufficient interfacial bonding strength between nano-cellulose and aluminum foil. Since the surface of nano-cellulose is rich in hydroxyl groups and shows hydrophilicity, while the surface of aluminum foil is relatively hydrophobic, there is obvious interfacial incompatibility between the two, resulting in weak interfacial bonding and easy delamination and peeling during actual use, affecting the thermal insulation performance and service life.

[0006] In the prior art, physical modification or chemical modification methods are often used to improve the interfacial bonding strength between different materials. Physical modification mainly includes mechanical treatment, plasma treatment, etc. Although the operation is simple, the modification effect is limited and the stability is poor. Chemical modification methods such as using coupling agents and graft copolymerization can improve the interfacial bonding at the molecular level, but often involve toxic and harmful chemical reagents, which do not meet the environmental protection requirements. In addition, the complex modification process will significantly increase the production cost and limit the large-scale application of the product.

[0007] Most of the nano-cellulose / aluminum foil composite non-woven materials on the current market use adhesives to composite each layer of materials. Although the process is simple, the interfacial bonding strength is relatively low, and the adhesive layer will affect the air permeability and flexibility of the materials. Therefore, developing a technical solution that can effectively improve the interfacial bonding strength between nano-cellulose and aluminum foil while maintaining the environmental protection and economy of the materials is of great significance for improving the performance and application value of nano-cellulose / aluminum foil composite non-woven insulation bags. Summary of the Invention

[0008] The purpose of the present invention is to provide a nano-cellulose / aluminum foil composite non-woven insulation bag and its preparation method, which solve the technical problem of insufficient interfacial bonding strength between existing nano-cellulose and aluminum foil, and improve the heat preservation performance and service life of the product.

[0009] To achieve the above purpose, the present invention provides a nano-cellulose / aluminum foil composite non-woven insulation bag, which includes the following components: Polypropylene non-woven fabric substrate; Composite interface layer, formed by nano-cellulose, metal-organic framework compound (MOFs) and cerium humate; Aluminum foil reflective layer.

[0010] The metal-organic framework compound (MOFs) and cerium humate form a synergistic interfacial structure, which improves the interfacial bonding strength between nano-cellulose and aluminum foil.

[0011] Among them, the gram weight of the polypropylene non-woven fabric substrate is 80-120 g / m 2 , and the thickness is 0.8-1.2 mm.

[0012] The metal-organic framework compound (MOFs) is selected from one or more of Zn-MOF, Cu-MOF, Al-MOF or Fe-MOF, and the dosage is 3-8 wt% of the mass of nano-cellulose.

[0013] The dosage of cerium humate is 2-6 wt% of the mass of nano-cellulose, and the molar ratio of Ce 3+ / Ce 4+ is 1:1 to 3:1.

[0014] The concentration of the nano-cellulose is 1.5-3.0 wt%, the fiber diameter is 20-50 nm, and the length is 0.5-2 μm.

[0015] The present invention also includes polyvinyl alcohol (PVA) adhesive, the concentration of which is 8-12 wt%, the degree of alcoholysis is 87-89%, the molecular weight is 44000-48000, and the dosage is 15-25 wt% of the total solid content.

[0016] The present invention also provides a method for preparing the above-mentioned nano-cellulose / aluminum foil composite non-woven insulation bag, which includes the following steps: (1) Mix the nano-cellulose aqueous dispersion with metal-organic framework compounds (MOFs), and disperse for 30-45 minutes at a rotation speed of 3000-5000 rpm; (2) Add cerium humate to the mixture in step (1), and continue to disperse for 15-20 minutes to obtain a functionalized nano-cellulose dispersion; (3) Dissolve polyvinyl alcohol in hot water at 80°C and stir until completely dissolved. After cooling to room temperature, add the functionalized nano-cellulose dispersion in step (2), and stir for 30-45 minutes to obtain a uniform slurry; (4) Use a coating device to uniformly coat the slurry in step (3) on the surface of the polypropylene non-woven fabric; (5) Place the coated non-woven fabric in an environment at a temperature of 60-80°C and dry for 30-60 minutes; (6) Compose the dried functionalized non-woven fabric and the aluminum foil through a hot pressing process, with a hot pressing temperature of 110-130°C, a pressure of 0.5-1.0 MPa, and a time of 3-5 minutes.

[0017] In step (2), before adding cerium humate, adjust the pH to between 5.5 and 6.5 to promote the formation of a coordination network structure between MOFs and cerium humate.

[0018] In step (6), before hot pressing and composing, perform plasma treatment on the surface of the aluminum foil, with a treatment time of 30-60 seconds and a power of 50-100 W to enhance the interfacial bonding strength.

[0019] In addition, this method also includes a step of post-treating the composite material. The post-treatment includes allowing the composite material to stand in an environment with a relative humidity of 60-70% for 12-24 hours to enable MOFs and cerium humate to form a rigid-flexible balanced interfacial network structure.

[0020] To better understand the present invention, the present invention makes a detailed explanation of the above-mentioned insulation bag and the preparation method as follows: 1. Analysis of basic principle From the perspective of molecular structure, the surface of nano-cellulose (CNF) is rich in hydroxyl groups (-OH), showing hydrophilic characteristics, while the surface of the aluminum foil usually has a layer of aluminum oxide (Al2O3) film, showing relatively hydrophobic properties. This interfacial polarity difference is the fundamental reason for the insufficient bonding strength between the two. As a traditional adhesive, polyvinyl alcohol (PVA) can form hydrogen bonds with nano-cellulose, but its interaction with the surface of the aluminum foil mainly relies on physical adsorption, and its interfacial bonding force is limited.

[0021] Traditional processes primarily attempt to improve interfacial bonding by adding a silane coupling agent (KH-550). The silane groups in the KH-550 molecular structure undergo a condensation reaction with the hydroxyl groups on the aluminum foil surface, while its amino end forms a chemical bond with the adhesive system. However, the effectiveness of this single coupling agent is limited by the complexity of the interfacial chemical environment, resulting in insufficient interfacial bonding and prone to delamination under stress.

[0022] 2. Synergistic Effect Analysis There is a significant synergistic effect between metal-organic frameworks (MOFs) and cerium humate. MOFs have a regular pore structure and extremely high specific surface area, while cerium humate has abundant oxygen-containing functional groups and coordination capacity. The synergistic effect produced by the combination of the two is mainly reflected in the following aspects: Multi-coordination network formation: Metal nodes in MOFs (such as Zn 2+ 、Cu 2+ The cerium humate (CiH) can form coordination bonds with the carboxyl and phenolic hydroxyl groups in the cerium humate molecules, building a three-dimensional network structure. This structure forms a molecular bridge between the nanocellulose and the aluminum foil, providing multiple connection points and enhancing the interfacial bonding strength.

[0023] Enhanced spatial stability: The rigid skeleton structure of MOFs and the flexible macromolecular chains of cerium humate are interwoven to form a semi-interpenetrating network, which not only maintains the spatial stability of MOFs but also utilizes the flexible properties of cerium humate, enabling the entire interface layer to disperse stress more evenly when subjected to force.

[0024] Optimization of the porous structure of the interface layer: The interface layer formed by the synergistic action of the two substances has a hierarchical porous structure. This structure not only increases the specific surface area of the material and increases the interface contact area, but also forms more air barrier layers during the insulation process, further improving the insulation performance.

[0025] Molecular interface mechanism: At the molecular level, the synergistic effect of MOFs and cerium humate creates a double anchoring effect: MOFs form coordination bonds with oxygen atoms on the surface of aluminum foil through the metal nodes in its rigid skeleton structure, providing strong chemical adsorption; Ce in cerium humate 3+ / Ce 4+ The ions can form coordination bonds with the hydroxyl groups on the surface of nanocellulose, and the cerium ions can also produce additional interactions with the organic ligands in MOFs; this dual anchoring effect enables the nanocellulose and aluminum foil to be tightly bound through the MOFs-cerium humate composite interface layer, forming a continuous chemical bond network and achieving effective connection.

[0026] 3. Comprehensive analysis of the mechanism In traditional cognition, the combination of MOFs and cerium humate has the following defects: Brittleness problem of MOFs: MOFs usually have a rigid crystal structure, which leads to an increase in the brittleness of the interfacial layer in flexible materials, reducing the flexibility and durability of the materials.

[0027] Redox property of cerium humate: Ce in cerium humate 3+ / Ce 4+ Redox pairs promote the oxidative degradation of materials, especially in composite materials containing organic components, accelerating the aging of the polymer matrix.

[0028] Poor compatibility between complex components: Mixing highly crystalline MOFs with amorphous cerium humate theoretically leads to phase separation, affecting the stability of the system.

[0029] Increase in hydrophilic components: Both MOFs and cerium humate have certain hydrophilicity, increasing the hygroscopicity of the thermal insulation material and reducing the long-term use performance.

[0030] However, in the patent system, these defects bring unexpected synergistic effects: Construction of a rigid-flexible balanced interfacial layer: The rigid framework of MOFs provides the necessary structural support in the interfacial layer, while the flexible macromolecular chains of cerium humate fill in between, forming a rigid-flexible combined interfacial layer; the interfacial layer structure has sufficient strength to resist deformation when stressed and also has a certain flexibility to absorb stress, avoiding brittle fracture caused by a pure rigid interface.

[0031] Redox synergistic protection mechanism: Ce in cerium humate 3+ / Ce 4+ Redox pairs form a synergistic redox system with metal nodes in MOFs; this system can capture reactive oxygen and free radicals in the environment, protecting nanocellulose and the polymer matrix from oxidative damage; cerium ions in cerium humate can also form stable Ce-O-Al bonds with the oxide layer on the surface of aluminum foil, reducing the further oxidation of aluminum foil and extending the service life of the material.

[0032] Interface compatibility enhancement mechanism: The crystal structure of MOFs and the functional groups in cerium humate form an interpenetrating network, avoiding phase separation; this composite structure forms a gradient transition layer at the interface between nanocellulose and aluminum foil, achieving a gradual structure from hydrophilic nanocellulose to relatively hydrophobic aluminum foil; the gradient interfacial layer reduces interfacial stress concentration, improving interfacial bonding strength and durability.

[0033] Synergistic heat insulation mechanism of the micro-porous structure: The regular pore channels of MOFs and the irregular microporous structure formed by cerium humate complement each other to construct a hierarchical pore structure. While maintaining good interfacial bonding, this structure can capture a large amount of static air, significantly improving the heat insulation performance of the material. The hierarchical pore structure also forms a maze effect for heat transfer, extending the heat conduction path and further enhancing the heat insulation effect.

[0034] Synergistic mechanism of moisture management: The controllable pore size structure of MOFs can selectively adsorb water molecules in a high-humidity environment, while the cerium ions in cerium humate can catalyze the redistribution of water molecules. This synergistic effect enables the material to maintain a relatively stable moisture content in a high-humidity environment, avoiding the significant impact of humidity changes on the heat insulation performance. Moderate moisture adsorption and management can also reduce the thermal bridge effect inside the material, further optimizing the heat insulation performance.

[0035] A multiple interaction network is formed between MOFs and cerium humate, as follows: Coordination bond network: The metal nodes in MOFs and the oxygen-containing functional groups in cerium humate form coordination bonds to construct a three-dimensional coordination network; Hydrogen bond interaction: The carboxyl groups, phenolic hydroxyl groups, etc. in cerium humate form hydrogen bonds with the organic ligands of MOFs, enhancing the interaction between the two; π-π stacking effect: π-π stacking is formed between the aromatic ring structures in MOFs and the aromatic structures in cerium humate, further stabilizing the composite structure; Electrostatic interaction: The electrostatic attraction between the positively charged cerium ions and the negatively charged regions of MOFs provides additional stability.

[0036] The multiple interactions jointly construct a highly integrated interfacial layer, which not only improves the bonding strength between nanocellulose and aluminum foil, but also endows the material with excellent heat insulation performance and service life.

[0037] The synergistic effect of metal-organic framework compounds (MOFs) and cerium humate in the nano-cellulose / aluminum foil composite non-woven insulation bag realizes the efficient bonding between nano-cellulose and aluminum foil by constructing a rigid-flexible balanced multifunctional interfacial layer, while optimizing the heat insulation performance and service life of the material.

[0038] In summary, the present invention has the following beneficial effects: By introducing two synergistic substances, metal-organic framework compounds (MOFs) and cerium humate, the present invention constructs an interfacial enhancement system, achieving a significant improvement in the interfacial bonding strength between nano-cellulose and aluminum foil, and having the following beneficial effects: Significant improvement in interfacial bonding strength: In the present invention, MOFs and cerium humate act synergistically to form a multiple coordination network structure, constructing a molecular bridge from nanocellulose to aluminum foil and significantly improving the interfacial bonding strength.

[0039] Optimization of thermal insulation performance: The regular pore channels of MOFs and the irregular microporous structure formed by cerium humate complement each other, constructing a hierarchical pore structure and enhancing the thermal insulation performance of the material.

[0040] Extended service life: The Ce 3+ / Ce 4+ redox pair in cerium humate and the metal nodes in MOFs form a synergistic redox system, which can capture reactive oxygen species and free radicals in the environment, protect the material from oxidative damage and extend its service life.

[0041] Improved environmental friendliness: The MOFs and cerium humate used in the present invention are both environmentally friendly materials, reducing the use of toxic and harmful chemical reagents in traditional processes and reducing the negative impact on the environment.

[0042] Reasonable production cost: Although new functional materials are introduced, through optimizing the process flow, the production cost of the present invention only increases slightly compared with the traditional process, while the performance is significantly improved. Description of the Drawings

[0043] Figure 1 is the Fourier transform infrared spectroscopy (FTIR) diagram; Figure 2 is the X-ray photoelectron spectroscopy (XPS) diagram. Detailed Embodiments

[0044] A method for preparing a nanocellulose / aluminum foil composite non-woven thermal insulation bag, the specific steps are as follows: (1) Preparation of nanocellulose / MOFs composite dispersion: Take 100 g of nanocellulose aqueous dispersion with a concentration of 1.5 - 3.0 wt% (fiber diameter 20 - 50 nm, length 0.5 - 2 μm), and add 3 - 8 wt% of Cu-MOF (HKUST-1, specific surface area 1500 m 2 / g, average pore diameter 1.5 nm) based on the mass of nanocellulose, and disperse it in a high-speed disperser at a rotation speed of 3000 - 5000 rpm for 30 - 45 minutes. Adjust the pH of the dispersion to 5.5 - 6.5.

[0045] (2) Preparation of functionalized nanocellulose dispersion: Add 4.5 wt% of cerium humate (Ce 3+ / Ce 4+The molar ratio is 1:1 to 3:1), and continue to disperse for 15 - 20 minutes to obtain a functionalized nanocellulose dispersion.

[0046] (3) Slurry preparation: Dissolve 70 g of an aqueous solution of polyvinyl alcohol (degree of alcoholysis 87 - 89%, molecular weight 44000 - 48000) with a concentration of 12 wt% of the total solid content in hot water at 80 °C and stir until completely dissolved. After cooling to room temperature, add the functionalized nanocellulose dispersion from step (2) and stir for 30 - 45 minutes to obtain a uniform slurry.

[0047] (4) Coating treatment: Use a doctor blade coater to uniformly coat the slurry from step (3) on the surface of polypropylene non - woven fabric (gram weight 110 g / m 2 , thickness 1.1 mm), and control the coating amount at 45 g / m 2 (wet weight).

[0048] (5) Drying treatment: Place the coated non - woven fabric in an oven and dry it at a temperature of 60 - 80 °C for 30 - 60 minutes until the moisture content is less than 4%.

[0049] (6) Aluminum foil lamination: Perform plasma treatment on an aluminum foil with a purity of 99.7% and a thickness of 12 μm (treatment time 30 - 60 seconds, power 50 - 100 W), and then laminate the treated aluminum foil with the dried functionalized non - woven fabric from step (5) through a hot - pressing process. The hot - pressing temperature is 110 - 130 °C, the pressure is 0.5 - 1.0 MPa, and the time is 3 - 5 minutes.

[0050] (7) Post - treatment: Let the composite material stand in an environment with a relative humidity of 60 - 70% for 12 - 24 hours to form a rigid - flexible balanced interfacial network structure between MOFs and cerium humate. Then cut and sew the material into a thermal insulation bag with dimensions of 35 cm × 45 cm × 20 cm.

[0051] The present invention designs the following experiments to verify the technical mechanism of the nanocellulose / aluminum foil composite non - woven fabric thermal insulation bag: 1. Experimental purpose and overview This experiment aims to comprehensively verify the synergistic mechanism of the metal - organic framework compound (MOFs) and cerium humate in the nanocellulose / aluminum foil composite non - woven fabric thermal insulation bag. Through designing multiple groups of control experiments and testing methods, systematically evaluate the interfacial enhancement effects of these two substances under different conditions, and verify their synergistic mechanism in aspects such as interfacial bonding strength, thermal insulation performance, and aging resistance. The experiment will focus on verifying the following aspects: (1) Multiple coordination network formation mechanism; (2) Rigid - flexible balanced interfacial layer construction mechanism; (3) Redox synergistic protection mechanism; (4) Synergistic thermal insulation mechanism of the micro - porous structure; (5) Influence of pH value on the synergistic effect.

[0052] 2. Experimental Grouping and Formulation Design 2.1 Experimental Grouping Design Seven experimental groups and three control groups were set up, and the specific formulations are shown in Table 1 below: Table 1: Experimental Design Table 2.2 Explanation of the Design Purpose of the Experimental Groups EG1 (Basic Experimental Group): The basic formulation was adopted as a benchmark for comparison with other groups; EG2 (High MOFs Group): The dosage of MOFs was increased to verify its effect on the formation of coordination networks; EG3 (High Cerium Humate Group): The dosage of cerium humate was increased to verify its effect on flexible structures and redox protection; EG4 (High Ce 3+ Group): The Ce 3+ / Ce 4+ ratio was adjusted to verify the redox synergistic protection mechanism; EG5 (Low pH Group) and EG6 (High pH Group): The pH value was adjusted to verify its effect on the formation of coordination networks; EG7 (Mixed MOFs Group): Different types of MOFs were mixed to verify the effect of different metal nodes on coordination networks; CG1 - CG3 (Control Groups): Control groups using traditional processes, MOFs alone, or cerium humate alone were set up to verify the synergistic effect.

[0053] 3. Experimental Design and Procedures 3.1 Sample Preparation Method Samples of all experimental groups and control groups were prepared according to the following unified procedures, with only differences in the formulation composition: 3.1.1 Preparation of Nano - cellulose / MOFs Composite Dispersion: 100 g of nano - cellulose aqueous dispersion with a concentration of 2.0 wt% (fiber diameter 30 nm, length 1.0 μm) was taken; the corresponding type and dosage of MOFs were added according to the formulations of each group; it was dispersed with a high - speed disperser at a speed of 4000 rpm for 35 minutes; the pH was adjusted to the experimental design value.

[0054] 3.1.2 Preparation of Functionalized Nano - cellulose Dispersion: The preset dosage of cerium humate (prepared according to the Ce 3+ / Ce 4+ ratio of each group) was added to the dispersion obtained in step 1; it was continuously dispersed for 18 minutes to obtain the functionalized nano - cellulose dispersion.

[0055] 3.1.3 Preparation of Slurry: Dissolve 80 g of an aqueous solution of polyvinyl alcohol (degree of alcoholysis 88%, molecular weight 46,000) with a concentration of 10 wt% in hot water at 80 °C; stir until completely dissolved, and cool to room temperature; add the functionalized nanocellulose dispersion in step 2, and stir for 40 minutes to obtain a homogeneous slurry.

[0056] 3.1.4 Coating treatment: Use a doctor blade coater to evenly coat the slurry on the surface of polypropylene non-woven fabric (gram weight 100 g / m 2 , thickness 1.0 mm), and control the coating amount at 40 g / m 2 (wet weight).

[0057] 3.1.5 Drying treatment: Place the coated non-woven fabric in an oven and dry it at 70 °C for 45 minutes; dry until the moisture content is less than 5%.

[0058] 3.1.6 Aluminum foil lamination: Perform plasma treatment (45 seconds, 75 W) on aluminum foil with a purity of 99.5% and a thickness of 10 μm; laminate the treated aluminum foil with the dried functionalized non-woven fabric through a hot pressing process; hot pressing conditions: temperature 120 °C, pressure 0.8 MPa, time 4 minutes.

[0059] 3.1.7 Post-treatment: Let the composite material stand in an environment with a relative humidity of 65% for 18 hours; cut it into standard test samples (5 cm × 10 cm) and small thermal insulation bags (20 cm × 25 cm × 10 cm).

[0060] 4. Experimental standards and experimental results 4.1 Interface bonding strength test Test standard: ASTM D1876 T-peel strength test; Test equipment: Universal material testing machine; Test conditions: room temperature (23 ± 2 °C), relative humidity 50 ± 5%, peeling speed 50 mm / min. Sample size: 25 mm × 150 mm. The experimental results are shown in Table 2 below: Table 2: Interface bonding strength test table 4.2 Thermal insulation performance test Test method: Determination of heat insulation time; Test equipment: Thermal insulation efficiency tester; Test conditions: Fill the thermal insulation bag with water at 25 °C and place it in an environment at 4 °C, record the time required for the water temperature to drop to 10 °C. Sample specification: Standard size thermal insulation bag (20 cm × 25 cm × 10 cm). The experimental results are shown in Table 3: Table 3: Heat Preservation Performance Test Table 4.3 Accelerated Aging Test Test Standard: ASTM G154 Ultraviolet Aging Test; Test Equipment: UV Aging Chamber; Test Conditions: 40 °C, Relative Humidity 80%, Ultraviolet Irradiation Intensity 0.68 W / m 2 ; Test Cycle: The test cycle is 24 hours, and record the time required for the peel strength to drop to 50% of the initial value.

[0061] The experimental results are shown in Table 4: Table 4: Aging Test Table 4.4 Thermogravimetric Analysis (TGA) Test Standard: ASTM E1131; Test Equipment: Thermogravimetric Analyzer; Test Conditions: Heating Rate 10 °C / min, Nitrogen Atmosphere, Temperature Range 25 - 600 °C; Sample Quantity: 10 ± 0.5 mg.

[0062] The experimental results are shown in Table 5: Table 5: Thermogravimetric Analysis Table 4.5 Fourier Transform Infrared Spectroscopy (FTIR) Analysis Test Standard: ASTM E1252; Test Equipment: FTIR Spectrometer; Test Conditions: Attenuated Total Reflection Mode (ATR), Scanning Range , Resolution , Scanning Times 32 times; Test Purpose: Verify the coordination effect between MOFs and cerium humate.

[0063] The experimental results are as Figure 1 shown, among which, the experimental data are shown in Table 6: Table 6: Infrared Spectroscopy Analysis Data Table 4.6 X-ray Photoelectron Spectroscopy (XPS) Analysis Test Standard: ISO 15472; Test Equipment: X-ray Photoelectron Spectrometer; Test Conditions: AlKα Ray Source, Vacuum Degree ; Test Purpose: Verify Ce3+ / Ce 4+ Proportion change and metal coordination state.

[0064] The experimental results are as Figure 2 shown, and the experimental data are shown in Table 7: Table 7: X-ray photoelectron spectroscopy analysis table 4.7 Specific surface area and pore size distribution test (BET) Test standard: ASTM D6556; Test equipment: Physical adsorption instrument; Test conditions: N2 adsorption, 77K, relative pressure range 0.05 - 0.30; Test purpose: To verify the formation of hierarchical pore structure.

[0065] The experimental results are shown in Table 8: Table 8: Specific surface area and pore size distribution table 4.8 Redox ability test Test method: Free radical scavenging ability test (DPPH method); Test equipment: UV-Vis spectrophotometer; Test conditions: Immerse the sample in DPPH solution and measure the change in absorbance at 517 nm; Test purpose: To verify the synergistic redox protection mechanism.

[0066] The experimental results are shown in Table 9: Table 9: Redox ability test table 5. Conclusion part Analysis of interfacial bonding strength: All experimental groups containing MOFs and cerium humate (EG1 - EG7) showed significantly better interfacial bonding strength than the control group, with the improvement rate ranging from 143% to 228%; the mixed MOFs group (EG7) and the high MOFs group (EG2) showed the highest interfacial bonding strength, which were 4.92 and 4.87 N / cm respectively; the pH value had a significant impact on the interfacial bonding strength, and the optimal value was around pH = 6.0.

[0067] Analysis of heat preservation performance: The heat preservation time of the experimental group was increased by 27 - 48% compared with the traditional process, and the mixed MOFs group (EG7) showed the best performance; the improvement of heat preservation performance was directly related to the specific surface area and pore structure of the material, and the mixed MOFs group showed the highest specific surface area and micropore ratio in the BET test.

[0068] Analysis of anti-aging performance: High Ce 3+Group (EG4) exhibited the best anti-aging performance with an aging time of 425 hours, which was 112.5% higher than that of the traditional process; the free radical scavenging rate test further confirmed the 3+ / Ce 4+ important influence of the ratio on antioxidant performance Microstructure and interfacial coordination analysis: FTIR and XPS results confirmed the formation of a coordination network structure between MOFs and cerium humate; the mixed MOFs group (EG7) showed the strongest peak shift and coordination bond characteristics in the FTIR test.

[0069] Multiple coordination network formation mechanism: The obvious shift of the O-H and C=O stretching vibration peaks observed in the FTIR test confirmed the formation of coordination bonds; the change of the Metal-O bond energy in the XPS test further confirmed the coordination between metal nodes and oxygen-containing functional groups; the experimental results showed that the mixed use of different types of MOFs (EG7) could form a stronger coordination network.

[0070] Verification of the mechanism for constructing a rigid-flexible balanced interfacial layer: The performance comparison between the high MOFs group (EG2) and the high cerium humate group (EG3) showed that the interfacial performance was optimal when the two were in a balanced ratio; the TGA test showed that the samples containing MOFs and cerium humate had higher thermal stability, confirming the formation of a rigid-flexible balanced structure Verification of the redox synergistic protection mechanism: The high Ce 3+ group (EG4) exhibited the best anti-aging performance and free radical scavenging ability; the XPS test confirmed the direct correlation between the Ce 3+ / Ce 4+ ratio and antioxidant performance; the free radical scavenging rate test further confirmed the redox synergistic effect between MOFs and cerium humate.

[0071] Verification of the mechanism for enhancing heat preservation by the micro-porous structure: The BET test results showed that the samples containing MOFs and cerium humate formed a hierarchical pore structure, and the specific surface area increased significantly; the proportion of micropore volume was positively correlated with the heat preservation performance, confirming the enhancing effect of the micro-porous structure on heat preservation performance; the mixed MOFs group (EG7) showed the optimal pore structure characteristics and heat preservation performance, verifying the synergistic effect of different types of MOFs.

[0072] Verification of the influence of pH value on the synergistic effect: The performance of the low pH group (EG5) and the high pH group (EG6) was lower than that of the basic group (EG1) with pH = 6.0; the FTIR and XPS test results showed that the pH value affected the formation strength of coordination bonds; the results confirmed that when the pH value was between 5.5 - 6.5, MOFs and cerium humate could form the best coordination network structure.

[0073] The experimental results fully confirm the strong synergistic effect between metal-organic frameworks (MOFs) and cerium humate. This synergistic effect is mainly achieved through the following mechanisms: Coordination network synergy mechanism: MOFs provide regular metal nodes, and cerium humate provides abundant oxygen-containing functional groups. The two form a complex three-dimensional coordination network, significantly enhancing the interfacial binding strength.

[0074] Rigid-flexible structure complementary mechanism: The rigid framework of MOFs and the flexible macromolecular chains of cerium humate interpenetrate each other to form an interfacial layer with both strength and toughness, avoiding the defects brought by single components.

[0075] Multi-level pore synergistic formation mechanism: The regular pores of MOFs and the irregular microporous structure formed by cerium humate complement each other to construct a multi-level pore structure, significantly improving the heat preservation performance of the material.

[0076] Redox dual protection mechanism: The Ce 3+ / Ce 4+ redox couple and the metal nodes in MOFs form a synergistic redox system to jointly capture reactive oxygen species and free radicals in the environment, greatly improving the anti-aging performance of the material.

Claims

1. A nano-cellulose / aluminum foil composite non-woven fabric thermal insulation bag, characterized in that, It includes the following components: Polypropylene non-woven fabric substrate; Composite interface layer, formed by nano-cellulose, metal-organic framework compound (MOFs) and cerium humate; Aluminum foil reflective layer; The metal-organic framework compound (MOFs) and cerium humate form an interface structure to improve the interfacial bonding strength between nano-cellulose and aluminum foil.

2. The nano-cellulose / aluminum foil composite non-woven fabric thermal insulation bag according to claim 1, wherein The grammage of the polypropylene non-woven fabric substrate is 80-120 g / m 2 , and the thickness is 0.8-1.2 mm.

3. The nano-cellulose / aluminum foil composite non-woven fabric heat preservation bag according to claim 1, wherein, The metal-organic framework compound (MOFs) is selected from one or more of Zn-MOF, Cu-MOF, Al-MOF or Fe-MOF, and the dosage is 3-8wt% of the mass of nano-cellulose.

4. The nano-cellulose / aluminum foil composite non-woven fabric heat preservation bag according to claim 1, wherein The dosage of cerium humate is 2-6 wt% of the mass of nanocellulose, and the molar ratio of Ce 3+ / Ce 4+ is 1:1 to 3:

1.

5. The nano-cellulose / aluminum foil composite non-woven fabric heat preservation bag according to claim 1, characterized in that, It also includes polyvinyl alcohol (PVA) binder, with a concentration of 8-12wt%, degree of alcoholysis of 87-89%, molecular weight of 44000-48000, and the dosage is 15-25wt% of the total solid content.

6. The nano-cellulose / aluminum foil composite non-woven fabric heat preservation bag according to any one of claims 1 to 5, characterized in that The concentration of the nano-cellulose is 1.5-3.0wt%, the fiber diameter is 20-50nm, and the length is 0.5-2μm.

7. A method for preparing a nanocellulose / aluminum foil composite non-woven thermal insulation bag according to any one of claims 1 to 6, characterized in that, It includes the following steps: (1) Mix the nano-cellulose aqueous dispersion with the metal-organic framework compound (MOFs), and disperse at a speed of 3000-5000rpm for 30-45 minutes; (2) Add cerium humate to the mixture in step (1), and continue to disperse for 15-20 minutes to obtain a functionalized nano-cellulose dispersion; (3) Dissolve polyvinyl alcohol in hot water at 80°C and stir until completely dissolved. After cooling to room temperature, add the functionalized nano-cellulose dispersion in step (2), and stir for 30-45 minutes to obtain a uniform slurry; (4) Use a coating device to uniformly coat the slurry in step (3) on the surface of the polypropylene non-woven fabric; (5) Place the coated non-woven fabric at a temperature of 60-80°C and dry for 30-60 minutes; (6) Compose the dried functionalized non-woven fabric and aluminum foil by hot pressing process, the hot pressing temperature is 110-130°C, the pressure is 0.5-1.0MPa, and the time is 3-5 minutes.

8. The preparation method according to claim 7, characterized in that, In step (2), before adding cerium humate, adjust the pH to between 5.5 and 6.5 to promote the formation of a coordination network structure between MOFs and cerium humate.

9. The preparation method according to claim 7, wherein In step (6), before hot pressing and compositing, perform plasma treatment on the surface of the aluminum foil, the treatment time is 30-60 seconds, and the power is 50-100W to enhance the interfacial bonding force.

10. The preparation method according to claim 7, wherein It also includes the step of post-treating the composite material. The post-treatment includes standing the composite material in an environment with a relative humidity of 60-70% for 12-24 hours to make MOFs and cerium humate form a rigid-flexible balanced interface network structure.